Urolithiasis in cats: Evaluation of trends in urolith composition and risk factors (2005‐2018) - Lucy Kopecny (Wiley, 2021)
Abstract Background Urolithiasis is an important upper and lower urinary tract disease in cats that results in morbidity and mortality. Objective To describe trends in composition of uroliths in cats and evaluate risk factors related to age, breed, sex, urolith location, and bacterial urolith cultures. Sample Population A total of 3940 uroliths and the cats from which they were obtained. Methods The database of the UC Davis Gerald V. Ling Urinary Stone Analysis Laboratory was searched for all urolith submissions from cats between January 2005 and December 2018. Mineral type, age, breed, sex, and urolith location and culture results were recorded. Trends were evaluated and variables compared to evaluate risk factors. Results A significant decrease in the proportion of calcium oxalate (CaOx)‐containing uroliths occurred over time (P = .02), from 50.1% (204/407) of all submissions in 2005 to 37.7% (58/154) in 2018. In contrast, the proportion of struvite‐containing uroliths increased significantly (P = .002), from 41.8% (170/407) in 2005 to 54.5% (84/154) in 2018. The proportion of CaOx‐containing uroliths in the upper urinary tract was significantly higher compared to the proportion of other urolith types in the upper urinary tract. Urate‐containing uroliths were the third most common type (361/3940, 9.2%). Overall, sex and age predispositions were similar to those reported previously. Conclusions and Clinical Importance The decrease in the proportion of CaOx‐containing uroliths and increase in the proportion of struvite‐containing uroliths warrants investigation. Further education regarding the efficacy of medical dissolution of struvite‐containing uroliths is recommended.